2018
DOI: 10.1007/s00772-018-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of incisional hernia after aortic aneurysm is not higher than after benign colorectal interventions

Abstract: BackgroundAbdominal aortic aneurysms (AAA) have most probably an inflammatory origin, whereby the elastica is the layer actually involved. In the past, collagen weackness was supposed to be the shared cause of both, AAA and incisional hernias. Since the development of new techniques of closure of the abdominal wall over the last decade, collagen deficency seems to play only a secondary etiologic role.ObjectivesThe aim of the study was to investigate whether the incidence of incisional hernia following laparoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These studies showed that the abdominal wall closure technique played a more critical role. [ 5 , 8 ] However, these studies are very few with relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that the abdominal wall closure technique played a more critical role. [ 5 , 8 ] However, these studies are very few with relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between procedures with medium incisions and the use of corticosteroids, immunosuppressive drugs, and smoking as factors of increased chance for complications are well established, especially on treatment of aortic aneurysms, diabetes and obesity [4,5]. Smoking increases the risk of infections, lung complications and surgical wounds.…”
Section: Introductionmentioning
confidence: 99%